2014
DOI: 10.1186/s40201-014-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Removal of amoxicillin from wastewater by self-made Polyethersulfone membrane using nanofiltration

Abstract: The present study investigated the performance of a self-made nanofiltration (NF) membrane for the removal of antibiotics from wastewater under changing operating conditions such as pH, initial feed concentration, operating pressure, and temperature. Amoxicillin (AMX) was used as one of the commonly prescribed antibiotics. A self-made NF membrane containing Polyethersulfone (PES), and Polyvinylpyrrolidone (PVP) was modified with Polyethylene glycol hexadecyl ether (Brij®58) surfactant. The self-made membrane w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Surfactants are surface-active agents, constituting the most important category of detergents [16]. For this purpose, various surfactants have yet been introduced, including but not limited to, Pluronic F127 [17], Tween 80 [18], Tween 20 [15], Tetronic 1307 [12], Triton X100, CTAB and SDS [19], Brij S100 [20] and Brij58 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are surface-active agents, constituting the most important category of detergents [16]. For this purpose, various surfactants have yet been introduced, including but not limited to, Pluronic F127 [17], Tween 80 [18], Tween 20 [15], Tetronic 1307 [12], Triton X100, CTAB and SDS [19], Brij S100 [20] and Brij58 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis using FTIR spectroscopy is meant to observe the chemical groups in the material. 31 Figure-1 presents the resulting IR spectra of the pure and Brij-blended PES membranes. The most distinguished structure of PES is denoted by the presence of SO 2 at 3096.11 cm -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Brij with a lower molecular weight is easily transported by the solvent and hindering the formation of porous structure during the membrane formation. 31,38 For the varying concentrations, it is observed that, for Brij with higher molecular weight, the concentration required to produce the highest water flux is smaller and may be seen on the membrane with the addition of Brij58 (Mw 1124 g/mol) and Brij98 (Mw 1149.56 g/mol). The highest PWF value was obtained from the addition of Brij at 7 wt%.…”
Section: Surface Hydrophilicity and Porositymentioning
confidence: 99%
“…Membrane process has been increasingly used in water and wastewater treatment, because these processes can successfully produce water of superior quality compared to conventional processes (1,2). The pressure-driven membranes are classified to four types: microfiltration (MF), ultrafiltration (UF), nanofiltration (NF), and reverse osmosis (RO).…”
Section: Definition and Classificationsmentioning
confidence: 99%